Turkish Translation and Patient Evaluation of the ASAS/EULAR Recommendations-Patient Version for the Management of Ankylosing Spondylitis - Salih Özgöçmen,; Mehmet Tuncay Duruöz, (Archives of Rheumatology, 2009)
Objective: The aim of this study was to evaluate the Turkish translation of the patient version of the Assessment in Spondyloarthritis International Society (ASAS) and European League Against Rheumatism (EULAR) recommendations for the management of ankylosing spondylitis (AS) by the patients. Material and Methods: Twelve members of the Ankylosing Spondylitis Patient Society of Turkey participated in the study. All were patients suffering from AS and all items of the recommendations were evaluated for the exact Turkish wording, meaning and comprehensibility by Turkish AS patients. All items were discussed and scored by the patients. Results: The median age of the 12 patients (4 female and 8 male) was 39.5 and disease duration was 11.5 years. The median Bath Ankylosing Spondylitis Disease Activity Index and Bath Ankylosing Spondylitis Functional Index were 4.0 and 3.42, respectively. Patients were agreed on each of the 10 items with a mean rate of >80%, and scored the overall recommendations with a mean score of 9.83±0.39. Conclusion: The patient version of the ASAS/EULAR recommendations for the management of AS has been successfully translated into Turkish and all of the patients reached an overall agreement on these recommendations. Treatment guidelines or recommendations that were composed using a medical language that could not be clearly understood by the patients should be translated into common vernacular in order to disseminate knowledge and maintain the patients' participation. (Turk J Rheumatol 2009; 24: 190-5)